2022
DOI: 10.1073/pnas.2114230119
|View full text |Cite
|
Sign up to set email alerts
|

Social reactivation of fear engrams enhances memory recall

Abstract: Significance Social interactions can bolster and protect memory performance. However, the relationship between social stimuli and individually learned memories remains enigmatic. Our work reveals that exposure to a stressed, naïve nonfamiliar conspecific or to the ambient olfactory–auditory cues of a recently stressed familiar conspecific induces reactivation of the cellular ensembles associated with a fear memory in the hippocampus. Artificially stimulating the hippocampal ensemble active during the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
(66 reference statements)
4
3
0
Order By: Relevance
“…Moreover, these reactivated cells were shown to be a functional component of the initially encoded memory as the direct modulation of engram activity via optogenetic stimulation or inhibition either facilitated or prevented the recall of an object memory. These findings are in support of previous work which has shown that engram activation is associated with the level of memory recall (2,46,53,54). In addition, they support a role for the hippocampus in object memory retrieval (55,56).…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Moreover, these reactivated cells were shown to be a functional component of the initially encoded memory as the direct modulation of engram activity via optogenetic stimulation or inhibition either facilitated or prevented the recall of an object memory. These findings are in support of previous work which has shown that engram activation is associated with the level of memory recall (2,46,53,54). In addition, they support a role for the hippocampus in object memory retrieval (55,56).…”
Section: Discussionsupporting
confidence: 91%
“…Altered (55). These findings are also in agreement with the current literature which has shown that engram activation is associated with the level of memory recall (1,46,(55)(56)(57). In addition, they also support a role for the hippocampus as a fundamental structure for object memory (58,59).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…Together, their studies show that socially rewarding and socially stressful situations modulate memory retrieval, use different populations of abGCs, and have distinct effects on neuronal activity in the DG. Finkelstein et al (2022) examined the effect that social interactions have on memory. They focused on the hippocampus and amygdala, which are both involved in memory formation and social behavior learning and memory formation ( Bliss and Lomo, 1973 ; Kandel and Tauc, 1965 ).…”
Section: Introductionmentioning
confidence: 99%
“…CreER can be expressed virally or in transgenic mice. Since 4-OHT leaves the body within a few hours, the labeling time window is significantly more precise than that of other methods such as the DOX-based system which is approximately a day long (5,(24)(25)(26). The use of these methods combined with immunohistochemistry (IHC) staining at the second time point in the memory task enables the study of new questions regarding the stability of engrams in reactivation and in the transition between memory stages.…”
Section: Introductionmentioning
confidence: 99%